Pengaruh Ice Breaking Terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas V SD Negeri 29 Pardomuan di Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Eva Silalahi; Rida Gultom; Pestaria Naibaho (LPPM Politeknik Pratama, 2023)
The purpose of this study is to determine how much influence Ice Breaking has on the Interest in Learning Christian Religious Education and Ethics of Class V Students of SD Negeri 29 Pardomuan I Learning Year 2023/2024. The research method used is descriptive quantitative method. The population is all grade V students of SD Negeri 29 Pardomuan I Learning Year 2023/2024 as many as 35 people. Data was collected using a positive closed questionnaire of 40 items, namely 25 items for variables X and 15 item for variable Y. The results of data analysis show that: a) positive relationship test obtained value rxy = 0.626 > rtabel(a=0.05,n=35) = 0.334 thus it is known that there is a positive influence between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.617 > ttable(a=0.05,dk=n-2=33) = 2.042 thus there is a significant relationship between variable X and variable Y. c) Regression equation test, obtained regression equation . d) Regression coefficient of determination test (r2) = 39%. e) Test the hypothesis using the F test obtained Fcalculate > Ftable=(a=0.05,dk numerator k=13,dk denominator=n-2=35-2=33) which is 20.58 > 2.09. So it can be concluded that there is a positive and significant influence of Ice Breaking on the Interest in Learning Christian Religious Education and Ethics of Class V Students of SD Negeri 29 Pardomuan I, Samosir Regency Learning Year 2023/2024 Keywords:,